Features of High-Quality Mathematical Training in the Context of Online Education of Students Oriented to Work in the Nuclear Industry - Vasilenko, N. P.; Chabanova, N. I. (Глобальная ядерная безопасность, 2022)
Due to the COVID-19 coronavirus infection pandemic, the world is faced with the need for social isolation and a forced rapid transition to a “home office” and online learning. The Russian education system has almost completely switched to distance learning. Working in the new conditions turned the daily routine of both teachers and students who not only faced difficulties of various nature but also discovered new opportunities for professional growth. Traditionally, it is customary to discuss the disadvantages of distance education, but this paper considers the advantages and new opportunities of this form of education. This is especially important in the process of mathematical training of university students focused on work in the nuclear industry due to the specifics and importance of studying this subject and due to the fact that at present online training is widely implemented in the training of employees of nuclear power plants where digitalization and everything which is associated with remote access technologies, thanks to the pandemic, are in demand and irreplaceable.